Animal models of focal ischemic stroke: brain size matters - Nowak, Blazej; Rogujski, Piotr; Guzman, Raphael; Walczak, Piotr; Andrzejewska, Anna; Janowski, Miroslaw (Frontiers in Stroke, 2023)
Stroke remains the second leading cause of death worldwide and the third cause of disability-adjusted life-years. Most strokes are ischemic in nature, meaning they are caused by the disruption of cerebral blood flow resulting from obstructed blood vessels. Reperfusion therapies such as thrombolysis with tissue plasminogen activator and endovascular mechanical thrombectomy are very effective and are becoming game changers for eligible patients. Despite these advances, the achieved effects are insufficient from the perspective of the entire population of stroke patients. Therefore, there is an urgent need to expand eligibility for reperfusion therapies and implement adjuvant therapeutic measures. Animal stroke models are at the forefront of these efforts, helping to untangle complex pathophysiology and providing valuable preclinical data to guide further clinical trials. Various stroke models are available, including direct blocking of cerebral arteries or using other means to recapitulate stroke pathophysiology. International advisory boards recommend initial in vivo experiments be performed in smaller animals, such as rodents. However, second testing would be more desirable in larger animals such as cats, pigs, dogs, and non-human primates. Due to larger cerebral volume, gyrencephalization, and higher white/grey matter ratio, large animals are crucial in translational stroke research. Animal stroke models differ in the time and complexity of the stroke induction procedure, the reproducibility rate, the level of similarity to the human condition, and the possibilities for analysis, imaging, and follow-up studies. The choice of the most appropriate stroke model may translate to better bench-to-bedside translation of preclinical stroke research